PENAEOID SHRIMPS (BENTHESICYMIDAE, ARISTEIDAE, SOLENOCERIDAE, SICYONHDAE) COLLECTED IN INDONESIA DURING THE CORINDON II AND IV EXPEDITIONS - Crosnier, Alain (Marine Research in Indonesia, 1984)
During the CORINDON II and IV expeditions, the former in the Makassar Strait and the latter in Piru Bay and Ambon Bay, Molluccas, 47 species of penaeoid shrimps were collected. They include 2 species belonging to the Benthesicymidae, 5 to the Aristeidae, 19 to the Solenoceridae, 2 to the Sicyoniidae and 19 to the Penaeidae.